Serum ferritin concentration and iron suppbments in patients with chronic renal failure - Inoue, Takashi; Monna, Takeyuki; Matsushita, Yoshiki; Morii, Hirotoshi; Miki, Takami; Kikunami, Kiichiro; Oda, Motoo; Hasegawa, Koichi (Jinko Toseki Kenkyukai kaishi. [Journal of the Dialysis Research Society, 1984)
Serum ferritin concentrations were measured by immunoradiometric assay in 20 healthy sublects and 15 undialyzed and 124 dialyzed patients with chronic renal failure. The mean level was lower in undialyzed patients, especially significantly lower in the female patients, than in healthy subjects. In dialyzed patients without iron supplement or blood transfusion the mean level was similiar to that in healthy male subjects, and the level was greatly increased by the iron supplement or blood transfusion. There was a significant inverse correlation between serum ferritin and TIBC, but there was no correlation between serum ferritin and serum iron or hematocrit in undialyzed and dialyzed patients. Serum ferritin was significantly lower and TIBC was significantly higher in the effective group than in the non-effective group before iron supplement in dialyzed patients. There was no significant difference in the levels of serum iron and hematocrit between the effective and non-effective groups. The serum ferritin level in the effective group rose more slowly than in the non-effective group following iron supplement. A significant correlation was noted between serum ferritin and serum iron, and no correlation between serum ferritin and hematocrit, after iron supplement. There was a significant correlation between the total dose of iron supplement and serum ferritin, TIBC, or serum iron, and also there was a significant correlation between the total volume of blood transfused and serum ferritin or serum iron. These findings indicate that serum ferritin may be the most reliable index to determine whether iron deficiency has been present or not, and that TIBC may be a more useful index for iron supplement than serum iron in patients with chronic renal failure. It is concluded that iron supplement is indicated when serum ferritin is lower than 100ng/ml, and when TIBC is higher than 280μg/dl.